Genotypic correlation between post discharge Clostridiodes difficle infection (CDI) and previous unit-based contacts. (March 2021) - Babady, N.E.; Aslam, A.; McMillen, T.; Syed, M.; Zehir, A.; Kamboj, M.
Summary: Background: Cases of Clostridiodes difficile infection (CDI) diagnosed after hospital discharge account for a substantial proportion of new infections. It is unclear whether post-discharge infections originate from hospital-based transmission. Methods: This was a Retrospective cohort study at a tertiary-care cancer center (non-outbreak setting). For all laboratory-identified cases of CDI in 2015–2016, patients with post-discharge (PD) CDI within eight weeks of their hospital stay were included in the study. Isolates from PD-CDI cases and their CDI-positive unit-based contacts were first genotyped by multilocus sequence typing (MLST). Common strains were further examined by core genome sequencing (CGS) to evaluate transmission links. Results: Of 173 cases examined by MLST, 50% of PD cases matched previous unit contacts. Next, 34 isolates, including 16 PD cases and their 18-unit contacts were examined by CGS. None were ≤3 single-nucleotide variants apart. Seventy percent of PD cases had in-hospital antibiotic exposure before CDI onset in the community. Conclusion: Our study results suggest that symptomatic CDI cases are not a substantial source of transmission to PD cases. Frequent antibiotic exposure in post-discharge CDI cases is an important target for surveillance and stewardship efforts.